Hello!
The first expression is
twice the difference between 6 times h and 3 gives 30.
twice the difference between 6h and 3=30
subtract:
2(difference between 6h-3)=30
2(6h-3)=30
Next:
Sum of 5 times z and 4 divided by 2 is 7.
Sum of 5z and 4 divided by 2=7
(5z+4)÷2=7
________________________________________________
next:
22 minus the product of 7 and y yields 1
22-7y=1
![\rule{300}{1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2w6ves65xgxja0frpmrqcic9efxxwpb93y.png)
Hope everything is clear.
#KeepLearning